National initiative for human development an innovative strategy to rehabilitate and develop human capital in Morocco - Ghmimed, Fatima; El Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2024)
Investment in human capital is one of the issues that societies of different systems and levels of growth are concerned with, as it has been proven that the human element is no longer only one of the elements of production, but is the main influence in all components of human development and its purpose, so that it has become at the forefront of the main measures of the wealth of nations, and then the importance and status of human development has increased on the basis that investing in people is the best type of investment because it is the solid and sound foundation for building a good and socially and economically strong society.In this context, the "National Initiative for Human Development", adopted by Morocco since 2005, is an advanced and bold step from a political perspective, a key lever for the benefit of vulnerable groups and an incentive for the possibilities in Moroccan cities and villages, as many interested people consider it a roadmap towards advancing sustainable development that includes all forms of disability, exclusion and marginalization, and integrating all community actors as a social and political element and actor in the development effort. Because it is based on the human being, it is fundamentally based on the principles of participation, consultation, partnership, contracting and transparency. Therefore, given these principles, the ambition is to become a reference in the field of good governance.Accordingly, this study aims to shed light on the general context of the National Initiative for Human Development in Morocco, its basics and foundations, the most important actors in its actions, as well as its programs and its role in the rehabilitation and development of human capital through the outcome of its achievements during the first and second phases (2005-2018).
Keywords: Development; National Initiative for Human Development; Human Development; Human Capital